Dimensão fractal de feridas dérmicas tratadas com fibrina rica em plaquetas autóloga e rosuvastatina em coelhos - Silva, Michel Fernando Bento da (2020)
Wound healing is a complex process divided into biological events and separated into four stages: hemostasis, inflammation, proliferation and remodeling. The use of biomaterials such as platelet-rich fibrin (FRP) in current procedures to improve tissue regeneration is directly related to reducing treatment time, improving scar quality and reducing the risk of rejection. The use of statins has been shown to be effective in the treatment of skin diseases. This pleiotropic effect suggests that statins can modulate cellular processes such as inflammation, apoptosis and proliferation. The fractal dimension (DF) is an analysis tool that allows more accurate measurement when compared to conventional histological methods. This study aimed to use DF to evaluate the collagen fibers of dermal wounds treated with autologous platelet-rich fibrin (aFRP) associated or not with rosuvastatin (RSV). Eight adult New Zealand male rabbits were used. In each rabbit, four equidistant incisions were made in the dorsal region. Each wound received a type of treatment: saline, aFRP, RSV and aFRP + RSV. The intact skin, removed at the time of the incision, was evaluated for comparison with the different treatments. Dermal samples were stained by Masson's trichrome and Picrosirius. The result of the DF analysis of the samples stained with Picrosirius in intact skin was lower (1.86 ± 0.06) when compared to the different treatments at 17° days (control 1.92 ± 0.02; aFRP 1.93 ± 0, 01; RSV 1.93 ± 0.02; aFRP + RSV 1.92 ± 0.01) indicating a greater concentration and organization of collagen fibers. There was no statistical difference between the treated groups. Based on the results, we concluded that DF was efficient for the evaluation of collagen, especially in slides stained with Picrosirius and can be an auxiliary tool in the evaluation of histological findings.